Enhanced Electrocatalytic Performance through Body Enrichment of Co‐Based Bimetallic Nanoparticles In Situ Embedded Porous N‐Doped Carbon Spheres. Issue 44 (10th September 2019) - Song, Qianqian; Li, Junqi; Wang, Shaolan; Liu, Junli; Liu, Xiaoxu; Pang, Lingyan; Li, Hu; Liu, Hui
Abstract: Extending available body space loading active species and controllably tailoring the d‐band center to Fermi level of catalysts are of paramount importance but extremely challenging for the enhancement of electrocatalytic performance. Herein, a melamine‐bridged self‐construction strategy is proposed to in situ embed Co‐based bimetallic nanoparticles in the body of N‐doped porous carbon spheres (CoM‐ e ‐PNC), and achieve the controllable tailoring of the d‐band center position by alloying of Co and another transition metal M (M = Ni, Fe, Mn, and Cu). The enrichment and exposure of the active sites in the body interior of porous carbon spheres, and the best balance between the adsorption of OH species and the desorption of O2 induced by optimizing the d‐band center position, collectively enhance the oxygen evolution reaction (OER) performance. Meanwhile, the relationship of d‐band center position and OER activity is found to exhibit the volcano curve rule, where the CoNi‐ e ‐PNC catalyst shows optimal OER performance with an overpotential of 0.24 V at 10 mA cm −2 in alkaline media, outperforming those of the ever‐reported CoNi‐based catalysts. Besides, CoNi‐ e ‐PNC catalyst also demonstrates high OER stability with slight current decrease after 100 h. Abstract : The enrichment and exposure of active sites in the surface and body interior of porous N‐doped carbon spheres, and the best balance between the adsorption of OH species and the desorption of O2 induced by the optimizing d‐band center position, collectively enhance the oxygen evolution reaction activity and stability.